Mobile Diabetes Education and Care: Intervention for Children and Youth with Type 1 Diabetes in Rural Areas of Northern Germany - Simone von Sengbusch (2009)
OBJECTIVE Intervention to improve quality of care of children with type 1 diabetes and limited access to speciality diabetes care in rural areas by a mobile diabetes education and care team, which is affiliated with a pediatric diabetes center of a university hospital. RESEARCH DESIGN AND METHODS A cohort study with 107 participating children and their families from eight rural hospitals was carried out between July 2000 and July 2002. Parameters on quality of metabolic control (HbA1c, hospitalisation rate and number of severe hypoglycemia), diabetes knowledge and quality of life at baseline (t0), six weeks (t1) and six months (t2) after the interventions were investigated.
Keywords: Diabetes mellitus; children; youth; rural areas